2008
DOI: 10.1038/ijir.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Oral phosphodiesterase-5 inhibitors and sperm functions

Abstract: This review aims to elucidate the possible effects of phosphodiesterase-5 (PDE5) inhibitors on sperm functions. PDEs hydrolyze cyclic nucleotides, and together with adenylyl and guanylyl cyclase, which catalyze the formation of cAMP and cGMP, regulate the levels of these second messengers in cells. cGMP-specific PDE5 is one of the PDEs that have been intensively studied because of its fundamental pharmacological relevance, as oral PDE5 inhibitors are used successfully in treating erectile dysfunction. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…The exact molecular events involved are not understood, but it was hypothesized that this acute effect could be due to changes in ionic channel or adenylyl and guanylyl cyclases, which catalyze the formation of cyclic AMP and GMP, respectively, and regulate the levels of these second messengers in cells of reservoir spermatozoa in epididymis and vas deferens (38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular events involved are not understood, but it was hypothesized that this acute effect could be due to changes in ionic channel or adenylyl and guanylyl cyclases, which catalyze the formation of cyclic AMP and GMP, respectively, and regulate the levels of these second messengers in cells of reservoir spermatozoa in epididymis and vas deferens (38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that PDE5 inhibitors could have a negative effect on male fertility by causing premature acrosome reaction [ 17 ]. Although studies have reported conflicting results about the influence of PDE5 inhibitors on sperm function, these data suggest the necessity of obtaining more reliable data about safety aspects related to the use of PDE5 inhibitors and fertilization process [ 18 19 ]. This is an especially important issue since the daily use of a PDE5 inhibitor has become a widespread regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular events involved are not understood but it was hypothesized that this acute effect could be due to changes in ionic channel or adenylyl and guanylyl cyclase, which catalyze the formation of cAMP and cyclic-guanosine monophosphate (cGMP), and regulate the levels of these second messengers in cells of reservoir spermatozoa in epididymis and vas deferens. [464748]…”
Section: Discussionmentioning
confidence: 99%